2022
DOI: 10.3390/ijerph192114261
|View full text |Cite
|
Sign up to set email alerts
|

High-Intensity Interval Training (HIIT) in Hypoxia Improves Maximal Aerobic Capacity More Than HIIT in Normoxia: A Systematic Review, Meta-Analysis, and Meta-Regression

Abstract: The present study aimed to determine the effect of high intensity interval training (HIIT) in hypoxia on maximal oxygen uptake (VO2max) compared with HIIT in normoxia with a Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA)-accordant meta-analysis and meta-regression. Studies which measured VO2max following a minimum of 2 weeks intervention featuring HIIT in hypoxia versus HIIT in normoxia were included. From 119 originally identified titles, nine studies were included (n = 194 partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 61 publications
1
12
0
Order By: Relevance
“…In addition, the increased aerobic demands under hypoxia concur with past studies documenting superior VO2 MAX development [11] and faster heart rate recovery [34] in basketball players after altitude training. The authors of [15] found that HIIT in hypoxia improved maximum aerobic capacity more than HIIT in normoxia.…”
Section: Effects Of Altitude On Internal and External Workloadmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, the increased aerobic demands under hypoxia concur with past studies documenting superior VO2 MAX development [11] and faster heart rate recovery [34] in basketball players after altitude training. The authors of [15] found that HIIT in hypoxia improved maximum aerobic capacity more than HIIT in normoxia.…”
Section: Effects Of Altitude On Internal and External Workloadmentioning
confidence: 98%
“…A few studies in basketball have shown the improvement of aerobic capacities [12], high-intensity running performance [13], and on-court high-intensity actions (sprints, jumps, change in direction, etc.) following hypoxic training [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…However, some perspectives have highlighted that previous studies did not consider the potential impact of variable training prescriptions [ 10 , 14 ]. Recent meta-analyses have also suggested that high-intensity interval training [ 33 ] or repeated sprint training [ 34 ] in a hypoxic condition can effectively improve performance or aerobic capacity in athletes. Training at different duration and intensities has been shown to place diverse physiological demands on the body, leading to potential differences in subsequent adaptive changes, irrespective of whether the environment is normoxic or hypoxic [ 28 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although adding hypoxia during interval training may result in greater performance gains compared with the same training performed in normoxia, 6 7 reductions in the intensities compared with the same training performed in normoxia have been reported during aerobic interval training in altitude. 8 Although, in general, interval training in hypoxia improves VO 2 max more than interval training in normoxia, 9 contradictory responses to the addition of hypoxia have been demonstrated depending on the variation of the interval training, 5 which may 6 7 or not 10 11 improve performance.…”
Section: Introductionmentioning
confidence: 99%